The impact of Heads Up testing on thrombectomy for acute ischemic stroke - Blackwood, Mallory; Beaman, Charles; Sharma, Latisha; Liebeskind, David S. (Frontiers in Stroke, 2025)
The Heads Up test, initially described in 2017, offers a potential tool for assessing likelihood of collateral failure in patients with acute large vessel occlusion (LVO) but low or resolving NIH who may become candidates for mechanical thrombectomy (MT). By raising the head of bed and performing serial exams (Heads Up test), detection of early symptomatic worsening may indicate vulnerability of collateral blood supply. The present study aims to examine the practical applications and outcomes of the Heads Up test in one institution over 9 years by analyzing 15 consecutive cases of documented Heads Up testing. Our findings suggest that the Heads Up test can provide valuable guidance in treatment decisions, but further data is needed to refine its criteria and applicability in the evolving neurointerventional practice.